Impact of Skeletal Expansion on the Soft Tissue of the Mid-face: A Prospective Study - Ibrahim S. Younis; Mustafa M. Alsultan (University of Mosul, College of Dentistry, 2024)
Aims: The study aimed to assess the midfacial soft and hard tissue changes of males and females following maxillary skeletal expansion in young adults. Materials and methods: 24 patients, 11 males, and 13 females (mean age, 19.54 years; between 17 to 27) with maxillary transverse deficiency treated with MSE. CBCT scans taken before and after expansion were used to measure the changes in soft and hard tissue landmarks. Paired t-tests were used for statistical analyses. Results: Hard tissue lower interzygomatic distance increased by (3.41mm in males, and 2.97mm in females), intermolar distance increased by (5.84mm in males, and 5.51mm in females), the palatal separation anteriorly was (4.14mm in males, and 3.76mm in females), posteriorly was (3.24 mm in males, and 3.25 mm in females), however nasal width increased by (3.49mm in males, and 3.29mm in females). Soft tissue average lateral movement of the alar curvature points was (2.1mm in males, and 1.98mm in females). the nasolabial fold width was (3.54mm in males, and 2.55mm in females). and interzygomatic width was (2.27mm in males, and 1.85mm in females). Conclusions: Maxillary expansion using MSE resulted in an almost parallel expansion with significant lateral movements of the soft tissues of the cheek and alar curvature points on both sides in young adults and it was correlated with the hard tissue changes.